MORPHOLOGICAL CHARACTERISTICS OF RENAL CORPUSCLES IN RATS - Kapustianska, A.A.; Chaykovskiy, Yu.B.; Shepitko, V.I.; Chelishvili, A.L. (World of Medicine and Biology, 2018)
One of the topical problems in modern morphology is studying the kidneys structure, which perform the excretion of metabolic products from the body, the regulation of the water balance and the amount and composition of most electrolytes, which ensure the stability of salt homeostasis and acid-base balance. In the research literature, data on the structural organization and morphological features of the kidney structure in intact animals are numerous, but this subject is still drawing attention of many researchers. Not the least role is played by understanding the features of structural and functional manifestations concerning the filtration barrier of the kidneys in various states.The purpose of the present research is to study the morphological characteristics of the renal corpuscles in intact rats and in control groups.The studies were carried out on kidneys taken from 32 rats of the Wistar line. The first group consisted of 5 intact animals; the second group (control) included 9 animals, which received 1 ml of physiological solution intraperitoneally; the third group (control) were 9 animals, subjected to a cut of the skin on the outer surface of the thigh with formation of a subcutaneous pocket with subsequent suturing of the wound; the fourth group (control) included 9 animals, injected 1 ml of physiological solution intraperitoneally, subjected to a cut on the outer surface of the thigh with formation of a subcutaneous pocket, followed by the wound suturing. Material for light microscopy of kidney components was prepared in accordance with generally accepted rules. The morphometric analysis was carried out using a semi-automatic graphic image processing device. The received digital data were processed by the method of variation statistics using the Student’s t-criterion.The performed histological studies of the kidneys’ cortical substance microscopic structure of intact rats have shown that it contains renal corpuscles, one of its main components, and epithelial tubules. The stroma of the organ is represented by layers of loose fibrous connective tissue, which is located between the tubules and surrounds the vessels.Renal corpuscles have a rounded form, consisting of a glomerular capsule and a renal corpuscle glomerulus. The capsule is shaped like a two-column bowl, built from the inner and outer walls, between which is the urinary space.Thus, there are superficial, intermediate and primozhnye renal organs that have a rounded form, glomerular capsule and vascular glomeruli. The capsule is shaped like a double-walled bowl, built of the inner and the outer walls, between which the urinary space is located. In animals of the control groups, no changes in the renal corpuscles structural components were detected due to the adaptive processes.
Keywords: kidneys; renal corpuscles; rats